Ayurvedic Management of Leiomyoma in Pregnancy-Case Study - Anila, M; Maragathavalli, P (International Research Journal of Ayurveda & Yoga, 2022)
Uterine myomas or fibroids are the most common benign female tumours of the reproductive organs, associated with significant effect on quality of life. The incidence of fibroid in pregnancy ranges from 0.1% to higher rates of 12.5%. Pregnancy is the one of the important time periods among the milestone of every woman. The care of a pregnant women from the time of conception till her delivery is a very delicate process. WHO has put forwarded a standard protocol for the care of pregnant woman, it’s called as Antenatal care. Any ailments occurring during this period should be very carefully managed as it may cause harmful effects on the growing fetus. Leiomyoma can cause pressure symptoms based on their size and position. This can aggravate the pedal odema or varicosities which are already a positive sign of pregnancy. Fibroid is considered as garbhashaya granthi in Ayurveda.The main dosas involved here is vata and kapha. In garbhini any type of sastra karma or anu sastra prayogas are contra indicated. So, the treatment should be vatakapha hara.For this drugs having praja sthapaka gunas should be selected.